Tree resin as a cultivation strategy under water deficit - Pimenta,Amanda Maria Leal (2021)
ABSTRACT The search for alternatives that enable the improvement of the soil water retention capacity should focus on a better water use by cultivated plants. This study aimed to evaluate the effect of natural tree resin rates and irrigation levels on the cotton (intermediate cycle) and wild radish (short cycle) crops. Two experiments were conducted in a completely randomized design, in a 5 × 5 factorial arrangement, with three replications and five tree resin rates (0, 0.67, 1.33, 2.00 and 2.67 g plant-1), five soil water tensions (15, 30, 45, 60 and 75 kPa) for cotton plants and five irrigation water levels (40, 60, 80, 100 and 120 % of the ETc) for wild radish plants. The plant height, stem diameter and number of leaves were evaluated at 93 days after sowing (DAS) for the cotton plants; while the plant height, root diameter and number of leaves were evaluated at 30 DAS for the wild radish plants, as well as quantified the shoot and root dry weights of both plant species. The application of tree resin reduces the susceptibility of the crop to water deficit, being 2.7 g plant-1 the highest recommended rate to improve the plant development. The use of tree resin increases the water-use efficiency in cotton and wild radish crops in up to 0.68 g L-1 and 69.6 g L-1, respectively.